2019
DOI: 10.1111/fme.12381
|View full text |Cite
|
Sign up to set email alerts
|

Diet and trophic role of octopus on an abalone sea ranch

Abstract: Gastric tract (crop and stomach) and stable isotope analyses (SIA) were used to evaluate the dietary composition of resident, commercially important Octopus aff. O. tetricus Gould, and its importance as a predator of Haliotis laevigata Donovan, on artificial abalone habitats. Taxonomic diversity and resolution of diet were higher in crops (13 taxa) than stomachs (10 taxa), with the latter dominated by unidentifiable material (%Volume = 74%). Crops contained mainly molluscs (~54%, including 31% abalone) and cru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 52 publications
1
4
0
Order By: Relevance
“…The slight shift in TL values between sites appeared to reflect a spatially varying consumption of predatory invertebrates. A similar mid-trophic position has been reported for Octopus tetricus consuming large volumes of abalone in a marine ranching food web (Greenwell et al, 2019). Earlier studies reported that GPOs are preyed upon by large fish, marine mammals (such as sea otters, harbor seals, sea lions, and killer whales), sharks, and even other octopuses (Haley, 1978;Hart, 1980;Gillespie et al, 1998).…”
Section: Trophic Niche Of E Dofleini In the Marine Ranching Food Websupporting
confidence: 65%
See 4 more Smart Citations
“…The slight shift in TL values between sites appeared to reflect a spatially varying consumption of predatory invertebrates. A similar mid-trophic position has been reported for Octopus tetricus consuming large volumes of abalone in a marine ranching food web (Greenwell et al, 2019). Earlier studies reported that GPOs are preyed upon by large fish, marine mammals (such as sea otters, harbor seals, sea lions, and killer whales), sharks, and even other octopuses (Haley, 1978;Hart, 1980;Gillespie et al, 1998).…”
Section: Trophic Niche Of E Dofleini In the Marine Ranching Food Websupporting
confidence: 65%
“…Its δ 13 C values were rather close to benthic-affinity prey, displaying a slight spatial variation. This result indicates an opportunistic feeding habit, which primarily exploits the most abundant prey type available (Vincent et al, 1998;Scheel and Anderson, 2012;Greenwell et al, 2019). The δ 13 C values of E. dofleini were similar to some teleosts, indicating an overlap in the primary carbon sources utilized between them (Kang et al, 2008).…”
Section: Trophic Niche Of E Dofleini In the Marine Ranching Food Webmentioning
confidence: 71%
See 3 more Smart Citations